Waveguide Filter Technology Characterization and Analysis - See, Wei Yang (Universiti Teknologi PETRONAS, 2021)
This thesis presented the design and simulation of 5G rectangular waveguide filter. The filtering function of the filter response is based on Chebyshev as it has the potential to be designed low volume and loss. Butterworth and Elliptic filter prototype are difficult to meet the specifications as mentioned above. Rectangular multi-mode filter is designed to reduce the filter size by introduce multiple resonances in one resonator while preserving its performance in power handling capability and losses. Methodology of realizing plausible work is done by different phases from design to verification stage. Based on Chebyshev polynomial, the coupling matrix is generated for obtaining the chained-function of the multiple-mode waveguide filter. For an example, a multi-mode rectangular waveguide filter operated in 4.1GHz with 250MHz bandwidth is designed and simulated in ANSYS High Frequency Structure Simulator (HFSS) software. It shows 0.15dB of low passband insertion loss, 16dB of good return loss and stopband rejection of 30dB at 3.3GHz, with 4 transmission poles and a pair of transmission zero are presented within the passband.